Hubungan Jarak Kehamilan dengan Kejadian Kekurangan Energi Kronis (KEK) Pada Ibu Hamil di Wilayah Kerja UPT Puskesmas Air Tiris Tahun 2026 - Endang Mayasari Mayasari; Nislawaty Nislawaty; Awari Susanti; Zurrahmi Z.R (Jurnal Ners, 2026)
Chronic Energy Deficiency (CED) in pregnant women remains a public health problem because it can increase the risk of complications for both mother and fetus. One of the factors assumed to be associated with CED is short interpregnancy interval, which may prevent the mother’s body from fully restoring its energy and nutrient reserves. This study aimed to determine the relationship between interpregnancy interval and the incidence of CED among pregnant women in the working area of UPT Puskesmas Air Tiris in 2026 . This study used a case-control design. The study population consisted of 52 pregnant women with CED as the case group and 469 pregnant women without CED as the control group. Case samples were selected using total sampling, while control samples were selected using simple random sampling, resulting in 52 respondents in each group. Data were analyzed using univariate and bivariate analysis with the Chi-square test at a 95% confidence level. The results showed that 36 respondents (69.2%) in the case group had a high-risk interpregnancy interval (<2 years), while 32 respondents (61.5%) in the control group had a non-risk interpregnancy interval. The Chi-square test indicated a significant relationship between interpregnancy interval and CED (p=0.003), with an Odds Ratio (OR) of 3.6 (95% CI: 1.59–8.10). It can be concluded that pregnant women with a high-risk interpregnancy interval have a 3.6 times higher risk of experiencing CED compared to those with a non-risk interval. Therefore, education on birth spacing, nutritional status monitoring, and antenatal care services should be strengthened to prevent CED among pregnant women.